Chapter 4. In the Scenario of Sustainable Mobility and Pandemic Emergency: Experiences of Bike- and E-Scooter-Sharing Schemes in Budapest, Lisbon, Rome and Vilnius - Diogo, Vera (2021)
"Within the collaborative economy, bike sharing and e-scooter sharing are relevant services that have been associated with increases in wellbeing, health (Woodcock et al., 2014) and quality of life, as well as with the creation of (often temporary) employment (De Groen et al., 2017),1 It is therefore important to understand the ways in which these sharing practices transform economic, social and cultural values related to mobility, and how they foster, rather than disrupt, social relationships. The impact of these services on the quality of urban life and on a mobility shift towards sustainability, is the specific focus in this chapter."